2021
DOI: 10.1007/s42832-021-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Continuous cropping of alfalfa (Medicago sativa L.) reduces bacterial diversity and simplifies cooccurrence networks in aeolian sandy soil

Abstract: Alfalfa is a perennial herbaceous forage legume that is remarkably and negatively affected by monocropping. However, the contribution of the changes in bacterial communities to soil sickness in alfalfa have not been elucidated. Therefore, we investigated bacterial community structures in response to monocropped alfalfa along the chronosequence. Continuous cropping remarkably reduced bacterial alpha diversity and altered community structures, and soil pH, total P and available P were strongly associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…The increase in available nutrients in this study, such as the soil AP and AK contents, may be largely associated with the increased abundance of phosphate- and potassium-solubilizing microbes under chitin amendments. This is substantiated by the increase of Streptomyces , Sphingomonas and Bacillus in this study ( Tables S9 , S10 ), which have the ability to solubilize phosphorus and potassium ( Chen et al., 2006 ; Xu et al., 2021 ). A surprising finding was that high dosages of crude chitin resulted in a substantial increase in soil -N content ( Table 1 ).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The increase in available nutrients in this study, such as the soil AP and AK contents, may be largely associated with the increased abundance of phosphate- and potassium-solubilizing microbes under chitin amendments. This is substantiated by the increase of Streptomyces , Sphingomonas and Bacillus in this study ( Tables S9 , S10 ), which have the ability to solubilize phosphorus and potassium ( Chen et al., 2006 ; Xu et al., 2021 ). A surprising finding was that high dosages of crude chitin resulted in a substantial increase in soil -N content ( Table 1 ).…”
Section: Discussionsupporting
confidence: 68%
“…The largest soybean production area in China is located in Heilongjiang Province, with the planting area increasing from 3.3 million ha in 2017 to nearly 6.8 million ha in 2022 ( Yin et al., 2017 ; Wu, 2022 ). Given that soybean is highly susceptible to continuous cropping ( Liu et al., 2019 ), an increasing frequency of soybean monoculture may result in extensive soil health deterioration and substantial losses of crop yield ( Liu et al., 2012 ; Xu et al., 2021 ). Previous studies have documented that biotic factors, rather than abiotic factors, are the main reasons for the occurrence of continuous cropping obstacles of soybean ( Dias et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Gaiella had shown a significant positive correlation with the continuous monoculture of Medicago sativa L . (alfalfa), whereas a significant negative correlation was observed with total phosphorus and available phosphorus content ( Xu et al, 2022 ). Beneficial taxa belonging to the genus Gaiella have been shown to suppress Fusarium wilt ( Zhao F. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Bradyrhizobium was decreased in the longterm continuous monoculture of Pinellia ternate, and it was suggested that it might be important for soil fertility and the removal of phenolic compounds (Zhao et al, 2021). The genus Gaiella had shown a significant positive correlation with the continuous monoculture of Medicago sativa L. (alfalfa), whereas a significant negative correlation was observed with total phosphorus and available phosphorus content (Xu et al, 2022). Beneficial taxa belonging to the genus Gaiella have Spearman's correlation between abundant bacterial genera and significant metabolites for CK vs. Y5 (A) and CK vs. Y20 (B).…”
Section: Metagenomic Profiling Of Bacterial Communitiesmentioning
confidence: 99%
“…Root rot is a destructive disease complex caused by several plant pathogenic fungi and oomycetes. Among these pathogens, Fusarium spp., and Rhizoctonia solani are the most damaging and frequently occurring root rot pathogens ( Anjanappa et al, 2016 ; Cao et al, 2020 ; Cai et al, 2021 ; Jiang et al, 2021 ; Xu et al, 2021 ; Zhao et al, 2021 ). In China, root rot is endemic in major alfalfa producing regions such as northwest China (Gansu, Xinjiang, Qinghai, Shaanxi, and Ningxia Huizu), north China (Hebei, Shanxi, and Inner Mongolia), and northeast China (Heilongjiang, Liaoning, and Jilin), with death rates of more than 60% on severe plots ( Fang et al, 2019 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%